Design and implementation of multiplication algorithm in quantum-dot cellular automata with energy dissipation analysis - Kamrani, Hamed; Heikalabad, Saeed Rasouli (The Journal of supercomputing, 2021)
QCA is an emerging nanotechnology for the design of digital system circuits based on electron interactions. QCA is used to design nanoscale circuits. Multiplier algorithms play an important role in computer computing, and algorithms with better performance speeds are more considerable. Booth multiplication algorithm is one of the multiplication algorithms that increases the multiplication speed by decreasing the number of partial products and using a smaller adder. In this paper, the Booth multiplication algorithm is designed and implemented in QCA. It has been tried to contain minimum number of cells and the least complexity and energy dissipation in the proposed design.